Novel Validated HPTLC Method for the Analysis of Two Binary Mixtures Containing Tamsulosin Hydrochloride with Antimuscarinic Agents. (11th September 2017) - El-Kimary, Eman I; Khamis, Essam F; Belal, Saeid F; Abdel Moneim, Mona M
Abstract: A validated and selective high-performance thin-layer chromatography (HPTLC) method was developed for the analysis of mixures of tamsulosin hydrochloride (TAM) with either tolterodine tartrate (TOL) or solifenacin succinate (SOL) in bulk drug and in combined dosage forms. The proposed method is based on HPTLC separation of the three drugs followed by densitometric measurements of their spots at 224 nm. Separation was carried out on Merck HPTLC aluminum sheets of silica gel 60 F254 using ethyl acetate–methanol–ammonia (6:4:0.05, v/v) as mobile phase. The linear regression analysis data were used for the regression line in the range of 0.1–0.7, 0.4–4 and 1–6 μg band –1 for TAM, TOL and SOL, respectively. The proposed method was validated and successfully applied for the analysis of their pharmaceutical formulations and laboratory-prepared mixtures containing the two bicomponent combinations. The method was validated and showed good performances in terms of linearity, sensitivity, precision, accuracy and stability.